Critical Discourse Analysis on Inter-Religious Marriages in a Luridical Sociological Review in Buntu Batu Village, Bastem District, Luwu Regency - Ernik; Andi sukmawati Assaad; Anita Marwing (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study employs Critical Discourse Analysis (CDA) to examine inter-religious marriages in Buntu Batu Village, Bastem District, Luwu Regency, through a juridical-sociological lens. Inter-religious marriages represent a complex intersection of legal frameworks, religious doctrines, and social practices that often generate tensions between individual rights and communal norms. This research investigates how discourse surrounding these marriages reflects and perpetuates power relations, ideological positions, and social hierarchies within the community. The juridical analysis explores the legal ambiguities and contradictions in Indonesian marriage law, particularly examining how Law No. 1 of 1974 on Marriage and subsequent regulations create obstacles for inter-religious couples. The study analyzes legal discourse that either facilitates or constrains inter-religious unions, revealing how juridical language constructs and maintains religious boundaries. The sociological dimension investigates community attitudes, family negotiations, and the lived experiences of couples navigating religious differences in Buntu Batu Village's multicultural context.  Through CDA methodology, this research deconstructs the dominant discourses surrounding inter-religious marriages, examining how language choices, narrative structures, and rhetorical strategies in legal texts, religious pronouncements, and community conversations either legitimize or delegitimize these unions. The analysis reveals how power operates through discourse to define acceptable marriage practices and construct religious identity boundaries.  Findings indicate that inter-religious marriages in Buntu Batu Village are shaped by competing discourses: legal formalism that emphasizes religious uniformity, religious orthodoxy that prohibits interfaith unions, and pluralistic perspectives that advocate for individual choice and tolerance. The study demonstrates how couples employ various discursive strategies—including conversion, administrative circumvention, and appeal to human rights frameworks—to navigate institutional barriers.  This research contributes to understanding how discourse shapes social reality in religiously plural societies, revealing the mechanisms through which legal and social systems either accommodate or resist religious diversity in intimate relationships. The findings have implications for policy development, interfaith dialogue, and promoting inclusive approaches to marriage regulation in multicultural contexts.